Quantitative image analysis of Tintin comics. (2017) - Parikesit, Gea Oswah Fatah
Digital image analysis is a very useful tool to perform humanities studies on various art forms, not only because it allows us to precisely quantify various parameters relevant for humanities scholars, but also because it provides us with new insights and perspectives that are not readily available from traditional qualitative methods. In this paper we demonstrate the application of this method, where we use the mean grey values and the number of edge pixels to represent the level of brightness and the level of visual details in the images, respectively, to characterise and identify various interesting properties of the images found in Tintin comics. Our results also indicate that this method can be used to characterise and identify different comics artists based on the visual patterns in their works.